2016
DOI: 10.1155/2016/1932532
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Intestinalα-Glucosidase and Glucose Absorption by Feruloylated Arabinoxylan Mono- and Oligosaccharides from Corn Bran and Wheat Aleurone

Abstract: The effect of feruloylated arabinoxylan mono- and oligosaccharides (FAXmo) on mammalian α-glucosidase and glucose transporters was investigated using human Caco-2 cells, rat intestinal acetone powder, and Xenopus laevis oocytes. The isolated FAXmo from wheat aleurone and corn bran were identified to have degree of polymerization (DP) of 4 and 1, respectively, by HPLC-MS. Both FAXmo extracts were effective inhibitors of sucrase and maltase functions of the α-glucosidase. The IC50 for FAXmo extracts on Caco-2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 48 publications
(60 reference statements)
1
51
0
Order By: Relevance
“…The type of compound conjugated to the phenolic acid appears not to affect their inhibitory potencies. Malunga and Eck () found that the inhibition potency of feruloylated arabinoxylan oligosaccharides were similar to that of ferulic acid at the same molar concentration. Interestingly, the redox potential of both caffeic and ferulic acid did not change when conjugated to other compounds (Teixeira et al, ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The type of compound conjugated to the phenolic acid appears not to affect their inhibitory potencies. Malunga and Eck () found that the inhibition potency of feruloylated arabinoxylan oligosaccharides were similar to that of ferulic acid at the same molar concentration. Interestingly, the redox potential of both caffeic and ferulic acid did not change when conjugated to other compounds (Teixeira et al, ).…”
Section: Resultsmentioning
confidence: 87%
“…The α‐glucosidase was obtained from rat intestinal acetone powder and inhibition of α‐glucosidase activity using maltose as a substrate was done according to a method described by Malunga and Eck () with modifications. Phenolic acids (20 M) were first dissolved in dimethyl sulfoxide (DMSO) and later diluted to 400 µM with sodium phosphate buffer (pH 6.9, 0.1 M).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, very recently, Malunga et al. described ferulic acid and feruloylated arabinoxylan mono‐/oligosaccharides as possible inhibitors of sucrase and maltase functions of α‐glucosidase in Caco‐2 and rat intestinal cells; moreover glucose uptake in Caco‐2 cells was partially inhibited by their presence .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-Glucosidase: Rat intestinal acetone powder was used in these assays, following established procedures [10][11][12][13][14] and testing inhibition by ethanol/HCl extracts from individual samples, diluted as appropriate in ethanol/HCl. Blanks were prepared in the absence of enzyme and of the ethanol/HCl mixture, whereas controls were complete reaction mixtures containing the appropriate volumes of the ethanol/HCl mixture used for extraction, but no bioactives.…”
Section: Enzyme Inhibition Studiesmentioning
confidence: 99%